Cavernous hemangioma arising from the gastro-splenic ligament: a case report. - Chin, K.; Khair, G.; Babu, P.S.; Morgan, D.R. (2009)
We present a rare case of a 45-year-old woman who presented with epigastric pain associated with early satiety and weight loss. Imaging revealed a large intra-abdominal mass in the epigastrium. Despite intensive investigations, including ultrasound scanning, computed tomography, upper gastrointestinal endoscopy, and percutaneous biopsy, a diagnosis could not be obtained. A histological diagnosis of cavernous hemangioma arising from the gastro-splenic ligament was confirmed after laparoscopic excision and histological examination of the intra-abdominal epigastric mass.